Social Control of Womenâ€™s Body as Cultural-Political Legitimation in â€œPutri Cinaâ€ Novel - Sartika, Resa; Susanto, Dwi; Wibowo, Prasetyo (Humaniora: Journal of Indonesia Culture and Society, 2021)
The research aimed to describe the depiction of the female bodyâ€™s domination as a form of political-cultural legitimacy raised in Sindhunataâ€™s work entitled Putri Cina. Michel Foucaultâ€™s theory of discourse was applied as the approach to reveal how sexuality was closely related to power practices. The discourse presented in the novel was dissected by qualitative methods, descriptive qualitative, and interpretative data analysis techniques. The results show that the two main characters of this novel are Chinese women who experienced oppression in Java. The existence of a cultural identity crisis, abjection, passivity, and not subversion represents the figure of alienated women. This perspective is intertwined with how indigenous men perceive Chinese women figures. Sindhunata describes the unequal construction of sexuality between men and women and the discrimination of the Chinese race as repeated during the kingdom era, pre-independence, to the New Order era.Â